Resting cardiac function in adolescent non-suicidal self-injury: the impact of borderline personality disorder symptoms and psychosocial functioning - Koenig, Julian; Gaber, Lena; Parzer, Peter; Resch, Franz; Kaess, Michael (Psychiatry research, 2017)
Vagally mediated heart rate variability (vmHRV) is reduced in borderline personality disorder (BPD). Non-suicidal self-injury (NSSI) is associated with comorbid psychopathology, in particular BPD. We aimed to examine differences in cardiac function (vmHRV and heart rate [HR]) comparing adolescents (12-17 years) engaging in NSSI (n=30) and healthy controls (n=30). Further, we aimed to determine clinical concomitants of cardiac function in patients with NSSI. Analyses showed no significant group differences on cardiac function. Controlling for a host of confounding variables resting state HR and vmHRV in adolescents with NSSI were significantly correlated with BPD symptoms and the current level of functioning.